The Arrogance of Power and Imperialism as Manifested in Trump's Media Talk A Critical Discourse Analysis - M. A. Al-Saeedi, Habeeb (Journal of College of Education, 2020)
The American political discourse on media, under the presidency of Trump, is characterized by arrogance of power and imperialism. President Trump always seeks to present the United States as the most global powerful nation, and to demonstrate himself as the best president ever created. To look down upon others and impose the American will is the strategy that Trump embraces more to deal with allies and enemies to achieve the American projects around the world.             The present investigation is a critical discourse analysis that aims at studying the manifestation of arrogance of power and imperialism in Trump's media talk. It focuses on how these two aspects are employed in the media talk of President Trump.            The findings of the current study show that Trump usually uses threatening, intimidating, instigating and criticism in the different types of media talk; i.e. television interviews, press conferences, electoral rallies and even in his tweets that clearly express his arrogance of power and imperialism.
Keywords: : CDA, media talk, Trump, arrogance of power, imperialism